2015
DOI: 10.15554/pcij.05012015.63.83
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anchor wedge dimensional parameters on posttensioning strand performance

Abstract: A lthough unbonded posttensioning for use in gravity load systems (for example, floor and roof slabs) has been available in the United States since the 1950s and standards exist for its application, 1-4 this construction method is increasingly being considered and applied in more extreme loading environments, such as in primary earthquake-resisting structural components (for example, primary shear walls and moment-resisting frames). Recent advances in the seismic application of unbonded posttensioning include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Kwon et al [1] proposed an anchorage device with lateral reinforcement to resist bursting stress and developed a modified equation of bearing capacity based on their experimental and analytical results. Walsh et al [2] showed that posttensioning of the anchor or wedges plays a significant role in anchorage performance by controlling the stress transfer from the tendon to the anchor and, based on experimental results, proposed wedge details that can improve performance. Kim et al [3] investigated the effects of steel fiber and steel reinforcements on the ultimate bearing strength of the local anchorage zone and compared the results of the experimental results with the design equation.…”
Section: Introductionmentioning
confidence: 99%
“…Kwon et al [1] proposed an anchorage device with lateral reinforcement to resist bursting stress and developed a modified equation of bearing capacity based on their experimental and analytical results. Walsh et al [2] showed that posttensioning of the anchor or wedges plays a significant role in anchorage performance by controlling the stress transfer from the tendon to the anchor and, based on experimental results, proposed wedge details that can improve performance. Kim et al [3] investigated the effects of steel fiber and steel reinforcements on the ultimate bearing strength of the local anchorage zone and compared the results of the experimental results with the design equation.…”
Section: Introductionmentioning
confidence: 99%
“…The configuration shown in Figure 3(A) adopts a high‐strength, rod‐chuck ratchet component. The details of the ratchet component are shown in Figure 3(B), which consisted of the left plate, middle plate, four high‐strength rods (HSRs), eight nuts, and four “chucks.” Each “chuck” consists of commercially available anchorage hardware used to anchor pretensioned strands during fabrication, 32 The left end of the four HSRs was anchored to the left plate using eight nuts, to enable the connection to resist compression or tension. Their right ends went through the four chucks, which were welded to the right side of the middle plate, and could slide through the plate when the rod was in compression.…”
Section: Configuration Of Tested Lp‐sced Bracementioning
confidence: 99%
“…To prevent this behavior, the studies have recommended maximum allowable strand strains for use in the design of jointed precast structures. Walsh et al (2015) showed that higherperforming PT anchors that allow greater strand strains without fracture can be achieved by slightly changing the anchor wedge geometry.…”
Section: Connections Splices and Anchoragesmentioning
confidence: 99%